JAVANESE REDUPLICATION: A STUDY ON PANGKUR JENGGLENG TV PROGRAM - Prasetyo, Agustinus Hardi (International Journal of Humanity Studies (IJHS), 2019)
This paper reported a small-scale research on Javanese reduplication found in Pangkur Jenggleng Padepokan Ayom Ayem TV program which was aired in a local TV station in Yogyakarta, Indonesia. Since only few studies are conducted to discuss Javanese reduplication, this study was conducted to fill in the gap in the literature by asking these two questions: a) What are the types of reduplications found in Pangkur Jenggleng Padepokan Ayom Ayem TV Programs? and b) What are the semantic functions or categories of those reduplications? The results of this study confirm the previous studies on Javanese reduplication which reported that full reduplication (without any lexical category changes) are more frequently used than other types of reduplications in Javanese language. This study also confirms the results of previous studies that the dominant semantic functions of Javanese reduplication are repetition and pluralization. Further studies on Javanese reduplication were suggested to gain more knowledge as well as to preserve the Javanese language.DOI:Â 10.24071/ijhs.2019.020207